Hubungan Koordinasi Mata Kaki dan Power Otot Tungkai Terhadap Tendangan Momtong Dollyo Chagi - Ngurah Adi Santika, I Gusti Putu; Cahya Prananta, I Gst Ngr Agung (Jurnal Porkes, 2022)
The purpose of this study was to find the relationship between eye-foot coordination and leg muscle power on momtong dollyo chagi kicks. This research is a correlational research that looks for the relationship between the independent and dependent variables. The number of samples is 30 students of Taekwondo Club Waringin Denpasar City, taken by purposive sampling technique where the sample criteria are 11-14 years old. The results obtained through a simple regression test the existence of a relationship between eye-foot coordination with momtong dollyo chagi kicks with an R value of 0,131. Through a simple regression test, there is a relationship between leg muscle power and momtong dollyo chagi kick with an R value of 0,159. Meanwhile, through the multiple regression test, there is no simultaneous relationship between eye-foot coordination and leg muscle power on momtong dollyo chagi kicks with an R value of 0,182. From the results of the discussion, it can be concluded that there is a relationship between eye-foot coordination with momtong dollyo chagi kicks, and there is a relationship between leg muscle power and momtong dollyo chagi kicks. However, there is no simultaneous relationship between eye-foot coordination and leg muscle power on momtong dollyo chagi kicks.